The speed of the sound wave in the medium, given the data is 3900 m
<h3>Velocity of a wave </h3>
The velocity of a wave is related to its frequency and wavelength according to the following equation:
Velocity (v) = wavelength (λ) × frequency (f)
v = λf
With the above formula, we can obtain the speed of the sound wave. Details below:
<h3>How to determine speed of the sound wave</h3>
The speed of the wave can be obtained as illustrated below:
- Frequency (f) = 600 Hz
- Wavelength (λ) = 6.5 m
- Velocity (v) =?
v = λf
v = 6.5 × 600
v = 3900 m
Thus, the speed of the sound wave in the medium is 3900 m
Learn more about wave:
brainly.com/question/14630790
#SPJ4
Only 10 Kg of secondary consumers can be supported by the ecosystem.
There exists such a thing as the 10% rule in the transfer of energy in biomass from one trophic level to another. This rule ultimately controls the mass of biomass that is available at the next higher trophic level.
This rule state that only 10% of the energy in biomass is transferred to the next trophic level. By this rule, only 10% of the energy in the plant material is transferred to the carnivore population. Therefore, only 10 Kg of secondary consumers can be supported by the ecosystem.
Learn more about trophic level: brainly.com/question/13267087
Answer:
v = 1.98*10^8 m/s
Explanation:
Given:
- Rod at rest in S' frame
- makes an angle Q = sin^-1 (3/5) in reference frame S'
- makes an angle of 45 degree in frame S
Find:
What must be the value of v if as measured in S the rod is at a 45 degree)
Solution:
- In reference frame S'
x' component = L*cos(Q)
y' component = L*sin(Q)
- Apply length contraction to convert projected S' frame lengths to S frame:
x component = L*cos(Q) / γ (Length contraction)
y component = L*sin(Q) (No motion)
- If the rod is at angle 45° to the x axis, as measured in F, then the x and y components must be equal:
L*sin(Q) = L*cos(Q) / γ
Given: γ = c / sqrt(c^2 - v^2)
c / sqrt(c^2 - v^2) = cot(Q)
1 - (v/c)^2 = tan(Q)
v = c*sqrt( 1 - tan^2 (Q))
For the case when Q = sin^-1 (3/5)::
tan(Q) = 3/4
v = c*sqrt( 1 - (3/4)^2)
v = c*sqrt(7) / 4 = 1.98*10^8 m/s
The answer is C. I searched it up and people keep on saying that it's B, which is incorrect. I found another question on Brainly where someone said that C was the answer and the person who asked the question said "Correct, thanks."
Answer:
a. keeps its speed for a short while, then slows and stops. slows steadily until it stops.
Explanation:
Since the tension in the rope, t is greater than the kinetic friction fk, the box is moving forward because there is a net force on it. That is, t - fk = f = ma.
Since there is a net force, there is an acceleration and thus an increasing velocity.
When the rope breaks, the tension, t = 0. So, t - fk = 0 - fk = -fk = ma'.
Now, the net force acting on the box is friction in the opposite direction. This force tends to slow the box down from its initial velocity at acceleration, 'a' until its velocity is zero, where it stops. Since the frictional force is constant, the acceleration, a' on the box is thus constant and the box undergoes uniform deceleration until its velocity is zero.
<u>So, the box keeps its speed for a short while, then slows and stops. slows steadily until it stops.</u>
So, the answer is a.